INCREASING READABILITY OF CONVENTIONAL MILLING MACHINE BY USING DIGITAL READOUT (DRO) TO SUPPORT JIG BORING PROCESS - Rahmat Subarkah; Ghany Heryana; Moch. Sholeh; Andi Ulfiana; Ade Sumpena; Hamdi; Irwandi (Sekolah Tinggi Teknologi Wastukancana, 2020)
The requirements of manufacturing process are increasing to deal with global competition. The demand of precise components to support industry of food, pharmaceutical, infrastructure, energy and transportation are increasing significantly. Facing these challenges, capacity and capability of conventional milling machine need to be improved, especially in term of readability of axis movements. This matter influences the accuracy, machining time and easiness of machining process particularly in jig boring process. Linear encoder and digital readout (DRO) have been implemented in this study. Furthermore, this study investigated the used of linear encoder and digital readout (DRO) in jig boring process. The accuracy and machining time were involved in this study. This study proofed that linear encoder and digital readout improved the accuracy and machining time. Moreover, it helps operators in order to determine the datum and machining process. Based on these advantages, it is concluded that the linear encoder and digital readout are recommended to be implemented in small and medium industrial manufacturer in order to enhance their competitiveness in global market.